A STUDY OF POPULATION GROWTH AND ITS SOCIETAL EFFECTS IN BALI LOCAL GOVERNMENT AREA OF TARABA STATE, NIGERIA - USMAN BITRUS, DANFULANI; SALAWU ABDULKADIR, SAIDU (FUDMA JOURNAL OF SCIENCES, 2023)
Human beings evolved under conditions of high mortality due to famine, diseases and relatively low fertility rate. In the recent years, human population has drawn attention to the global issues because of the alarming growth rate. The study focused on growth rate of human population and its societal effects. A questionnaire was developed and administered among 389 respondents selected for the study. Also population figures of the area of study was obtained from 2006 National Population Bulletin and information from settlement, farm land, vegetation, build-up, water and others were obtained through Global Positioning System (GPS). The statistical analysis used for the study includes correlation, analysis of variance, and exponential  modelling and simulation study. The results of the analysis showed that the settlement, water usage and farm land increases while vegetation reduces in years 1986, 2005 and 2012.The simulation studies carried out because of availability of relevant data showed an exponential trend of population growth. A population projected indicated a carrying capacity of 322,160 people in the next 30 years and a growth rate of 1.81%. We recommended that the local government should consider population growth at all level of education in its budget. There should be a study of population growth at every level of education; social amenities should be increased as the population increases. The study also recommends for the evaluation of technological, pollution and the social trends on a vital coefficient and the fertility rates for at most 3 years to determine the variation in the population growth.
Keywords: Population; Growth; Society; Effects